Body Composition and Its Impact on Physical Fitness, and Cardiovascular Risk: A Literature Review - samuel martins; Siti Rahayu Nadhiroh; Pedro Amaral; Duarte Maubuti; Yopi Yeremia Alexander; Paradita Viola Ristianita; Asyifa Salsabilah Rahmi (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction: Body composition, including fat and lean mass, is recognized as a critical factor influencing physical fitness and cardiovascular health. Traditional measures such as body mass index do not distinguish fat from muscle and may misrepresent cardiometabolic risk. Objectives: This review analyzed recent evidence on the relationship between body composition, physical fitness, and cardiovascular risk to inform more accurate approaches to screening and prevention. Methods: A literature search was conducted in PubMed, Scopus, and Google Scholar for studies published between January 2020 and December 2025. Eligible studies included original articles, systematic reviews, or meta-analyses on adults. Titles, abstracts, and full texts were screened with inclusion and exclusion criteria. Data were extracted on study design, population, body composition methods, outcomes, and key findings. Narrative synthesis was performed. Results: Eight studies were included. Large cross-sectional analyses showed strong associations between body composition indicators, visceral fat, fat percentage, and lean mass, with blood pressure, lipid profile, and glucose regulation. Southeast Asian studies highlighted links between higher body fat, reduced physical activity, and increased cardiometabolic risk. Research in Brazil and the United States indicated that inflammatory markers and diet modified the relationship between adiposity and cardiovascular risk. Smaller studies emphasized the protective role of lean mass and physical activity, including technology-based exercise, on fitness and body composition outcomes. Conclusions: Body composition is a more accurate determinant of physical fitness and cardiovascular risk than body mass index. Integrating body composition analysis into clinical and public health practice could improve risk stratification and guide personalized preventive strategies.